Isolation of infectious SARS-CoV-2 from urine of a COVID-19 patient - Jing Sun; Airu Zhu; Heying Li; Kui Zheng; Zhen Zhuang; Zhao Chen; Yongxia Shi; Zhaoyong Zhang; Si-bei Chen; Xuesong Liu; Jun Dai; Xiaobo Li; et al. (Emerging Microbes and Infections)
SARS-CoV-2 caused a major outbreak of severe pneumonia (COVID-19) in humans. Viral RNA was detected in multiple organs in COVID-19 patients. However, infectious SARS-CoV-2 was only isolated from respiratory specimens. Here, infectious SARS-CoV-2 was successfully isolated from urine of a COVID-19 patient. The virus isolated could infect new susceptible cells and was recognized by its’ own patient sera. Appropriate precautions should be taken to avoid transmission from urine.